HAK ASASI MANUSIA TERHADAP HAK PEREMPUAN DALAM HUKUM ISLAM - Ichsan, Muhammad; Pasaribu, Yunita (JIMR : Journal Of International Multidisciplinary Research, 2025)
Women and their struggle for rights in society are always highlighted by researchers in their studies, with issues of inequality, patriarchy, and double burden being central themes, including in relation to women's rights in Islamic studies. This research aims to understand the concept of women's human rights from the perspective of Islamic law. The method used is descriptive qualitative with the use of library research. In library research, the method used to collect research data consists of selected, searched, presented, and analyzed library data. The result of this research is that women's rights are always protected by Islamic law; however, deeply entrenched social, cultural, traditional, and political norms build biases against women's rights, under the pretext of Islamic dictates. Considering the above findings, it is recommended that awareness be increased regarding women's rights under Islamic law. This research contributes to the issue of uplifting the dignity and status of women within families and communities, so that issues of inequality and other accompanying matters do not become prolonged problems without clear solutions.